1985
DOI: 10.1007/bf00688640
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial myopathy ?A result of clofibrate/etofibrate treatment?

Abstract: A 66-year-old man had developed a myopathy while undergoing several periods of etofibrate and clofibrate therapy over the past 5 years. Discontinuation of etofibrate treatment failed to reverse his muscle illness which, however, did not progress. A muscle biopsy revealed a chronic myopathy marked by abundant, abnormally structured muscle mitochondria. His mitochondrial myopathy may represent a forme fruste of the Kearns-Sayre syndrome or other types of mitochondrial myopathy, clinically made evident by the eto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Statins inhibit the HMG-CoA-reductase resulting in lower intracellular cholesterol levels.This later is an important component of cell membranes modulating their fluidity [1][2][3][4][5] . Myotoxicity associated to the use of statin is complex, involving mechanisms on the structure and function of the cellular membrane, mitochondrial dysfunction, and changes in the duplication of the myocyte [1][2][3][4][5][6][7][8][13][14][15] . A reduction in plasmatic and intracellular cholesterol can result in reduced levels of the membrane cholesterol leading to physical changes in this and a decrease in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins inhibit the HMG-CoA-reductase resulting in lower intracellular cholesterol levels.This later is an important component of cell membranes modulating their fluidity [1][2][3][4][5] . Myotoxicity associated to the use of statin is complex, involving mechanisms on the structure and function of the cellular membrane, mitochondrial dysfunction, and changes in the duplication of the myocyte [1][2][3][4][5][6][7][8][13][14][15] . A reduction in plasmatic and intracellular cholesterol can result in reduced levels of the membrane cholesterol leading to physical changes in this and a decrease in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in the various manifestations of toxic myopathies, the vacuolar and mitochondrial changes are usually painless, and with raised CK 13 as seen in cases 1,2,5, and 6, or even normal CK 12 . In cases with rapid onset, muscular pain tends to predominate 13 , however weakness in proximal musculature predominated in two of our cases (cases 2 and 8).…”
Section: Discussionmentioning
confidence: 99%
“…The main clinical related myopathies [ 11]. Statins inhibit synthesis of mevalonate, a precursor of adverse effects of statins are muscular and include elevation of serum creatine kinase, sometimes associated both cholesterol and ubiquinone.…”
Section: Introductionmentioning
confidence: 99%
“…syndromes related to fibrate therapy have mentioned mitochondrial abnormalities in muscle [11,31 ]. The hypothesis of a mitochondrial dysfunction induced by Ubiquinone determinations fibrate therapy still needs to be substantiated.…”
Section: Introductionmentioning
confidence: 99%
“…1991 Accepted: Februar. 10,1992 id-lowering agent, bezafibrate, a clofibrate analog. This syndrome occurred in subjects with normal as well as impaired kidney function [5,6], Pharmacokinetic investi gations of bezafibrate in patients with chronic uremia showed that the half-life is significantly prolonged and renal clearance is markedly decreased [7], On the basis of these data, a dose adjustment has been suggested in patients with renal impairment.…”
Section: Introductionmentioning
confidence: 99%